The Meta Discursive Dimension In Evaluative Practices And Improvement Of Writing Competence In French As A Foreign Language (Journal of Namibian Studies : History Politics Culture, 2024)
This research aims to understand better the role of metadiscursive feedback in improving the writing skills of FLE learners, taking into account teachers’ different interventions and their impact on students’ writing.Based on a corpus of 42 drafts written by Algerian students in the third year of secondary school, the study seeks to identify how traces of rewriting reveal students’ ability to adjust their discourse according to their teachers’ expectations, explicit or implicit. The analysis also examines how teachers use these traces to effectively guide students in improving their written productions.